Resiliensi dan Perilaku Merokok pada Remaja: Tinjauan Sistematis - Delly Arfa Syukrowardi; Junaiti Sahar; Astuti Yuni Nursasi; Imami Nur Rachmawati; Bahrul Hayat (Universitas Faletehan, 2025)
The high prevalence of smoking among adolescents poses a significant global health challenge. While resilience has been identified as a protective factor against risky behaviors, the underlying mechanisms and influencing factors have not been comprehensively synthesized. This study aimed to examine the relationship between resilience and smoking behavior among adolescents and to identify the mediating factors of this relationship through a systematic review. A systematic review design was employed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A comprehensive literature search was conducted across ScienceDirect, PubMed, ProQuest, and Scopus databases without publication year restrictions. The methodological quality of the included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Analytical Cross-Sectional Studies. Of the 326 articles identified, 10 studies met the inclusion criteria. The results indicated that high levels of resilience were significantly associated with lower rates of smoking behavior among adolescents. Resilience functions as a protective factor through the interaction between internal assets and external resources. Family support, school connectedness, positive peer support, and mental well-being were identified as key mediating factors that strengthen resilience in preventing smoking initiation. This study concludes that health promotion strategies and nursing interventions should not only focus on the dangers of smoking but also integrate resilience-building through a holistic approach involving family and school environments.